2001
DOI: 10.1177/088506660101600602
|View full text |Cite
|
Sign up to set email alerts
|

The Vessel Dilator for Central Venous Catheter Placement: Forerunner for Success or Vascular Misadventure?

Abstract: The vessel dilator for central venous catheter placement: forerunner for success or vascular misadventure? J Intensive Care hled 2001;16:263-269.During placement of a central venous catheter (CVC), the vessel dilator and/or combination dilator/sheath-introducer are recognized as potential causative agents in numerous traumatic complications that may be erroneously ascribed to the catheter, placement needle, or guidewire. A review of the literature and device-user sun-eyare offered in support of the need for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Nevertheless, internal jugular catheterization generally carries risks of mechanical complications such as pneumothorax, hemothorax, and arteriovenous fistula associated with arterial puncture [ 6 ]. Additionally, a previous report has shown that mechanical complications can also occur when using dilators for insertion of large-diameter sheaths [ 7 ]. The use of ultrasound guidance has been shown to reduce the risk of these mechanical complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, internal jugular catheterization generally carries risks of mechanical complications such as pneumothorax, hemothorax, and arteriovenous fistula associated with arterial puncture [ 6 ]. Additionally, a previous report has shown that mechanical complications can also occur when using dilators for insertion of large-diameter sheaths [ 7 ]. The use of ultrasound guidance has been shown to reduce the risk of these mechanical complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical complications such as hemothorax, cardiac injury, and arteriovenous fistula can occur when using a dilator. 6 Dilators that are used for insertion of large-bore catheters are stiffer and thicker than those used for insertion of conventional catheters. A thick dilator can damage blood vessels other than the target vessel.…”
Section: Discussionmentioning
confidence: 99%